2016
DOI: 10.3136/fstr.22.297
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of Water-soluble Pectin during Unrefined Tea Processing: Content and Molecular Weight Distribution

Abstract: We examined the dynamics of water-soluble pectin (WSP), specifically the content and molecular weight distribution, in tea leaves and tea infusions in relation to steaming time during unrefined tea processing. It was revealed that the fraction of higher-molecular weight (MW) WSP in tea leaves was infused at the beginning of unrefined tea processing at all steaming times, and lower-MW WSP was not infused during any processing steps.Moreover, by increasing steaming time, the increase of higher-MW WSP content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Unroasted and roasted tea leaves were powdered using a ZM200 cyclone sample mill (Retsch GmbH, Haan, Germany). Preparation of Alcohol-Insoluble Substances (AIS), WSP and HSP extraction from AIS, and determination of WSP and HSP contents by the colorimetric method were conducted using the 3,5-dimethylphenol method as described previously (Hirono and Uesugi, 2014;Hirono 2016). The extraction method is briefly described as follows: AIS was prepared by washing powdered tea leaves using 70% ethanol until the remaining free sugars were below 20 μg/mL of D-glucose.…”
Section: Determination Of Wsp and Hsp Contents In Tea Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unroasted and roasted tea leaves were powdered using a ZM200 cyclone sample mill (Retsch GmbH, Haan, Germany). Preparation of Alcohol-Insoluble Substances (AIS), WSP and HSP extraction from AIS, and determination of WSP and HSP contents by the colorimetric method were conducted using the 3,5-dimethylphenol method as described previously (Hirono and Uesugi, 2014;Hirono 2016). The extraction method is briefly described as follows: AIS was prepared by washing powdered tea leaves using 70% ethanol until the remaining free sugars were below 20 μg/mL of D-glucose.…”
Section: Determination Of Wsp and Hsp Contents In Tea Leavesmentioning
confidence: 99%
“…During unrefined tea manufacturing processes, it has been observed that the water-soluble pectin (WSP) content in tea leaves increases during the steaming process, which is in the initial stages of tea processing, via non-enzymatic β-elimination degradation, and steaming time proportionally influences the increase of WSP content in tea leaves and pectin content in tea infusions (Takayanagi et al, 1987a;Takayanagi et al, 1987b;Matsuo et al, 2012;Hirono and Uesugi, 2014;Hirono, 2016). During green tea manufacturing, pectin might be degraded by heating during the roasting process in refined tea manufacturing as is degraded during the steaming process in unrefined tea manufacturing.…”
Section: Introductionmentioning
confidence: 99%